1987
DOI: 10.1017/s0003356100018808
|View full text |Cite
|
Sign up to set email alerts
|

The effect of winter shearing of housed pregnant ewes on food intake and animal performance

Abstract: 1987). The effect of winter shearing of housed pregnant ewes on food intake and animal performance. ABSTRACTThe effects of winter shearing on the food intake and performance of housed ewes was studied in a series of three experiments. Winter shearing resulted in a proportional increase of dry-matter intake in ewes of 0-16 and 0-43 on two silage-based diets, of 0-09 on swede-based diets, but of only 0-02 on a hay-based diet. Shearing increased intake by a greater amount in smaller ewes and a similar trend occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 14 publications
5
16
0
Order By: Relevance
“…Kennedy (1985) reported that the food intake of cold-exposed sheep was increased proportionately by 0.13, which was attributed to an increased rate of eating and clearance of digesta from the rumen. Whilst temperature of the ewes in the current study was not recorded, it has been noted previously that shearing decreased the skin and rectal temperature (Vipond et al, 1987). Skelton and Huston (1968) reported a depression in food intake due to heat stress.…”
Section: Effects Of Winter Shearingmentioning
confidence: 49%
See 2 more Smart Citations
“…Kennedy (1985) reported that the food intake of cold-exposed sheep was increased proportionately by 0.13, which was attributed to an increased rate of eating and clearance of digesta from the rumen. Whilst temperature of the ewes in the current study was not recorded, it has been noted previously that shearing decreased the skin and rectal temperature (Vipond et al, 1987). Skelton and Huston (1968) reported a depression in food intake due to heat stress.…”
Section: Effects Of Winter Shearingmentioning
confidence: 49%
“…The increased food intake due to winter shearing has been reported previously (Vipond et al, 1987;Black and Chestnutt, 1990a) and persisted until lambing, probably due to the removal of the fleece increasing heat production to maintain body temperature post shearing and a reduction in heat stress in late pregnancy. Kennedy (1985) reported that the food intake of cold-exposed sheep was increased proportionately by 0.13, which was attributed to an increased rate of eating and clearance of digesta from the rumen.…”
Section: Effects Of Winter Shearingmentioning
confidence: 83%
See 1 more Smart Citation
“…The higher feed intake (DMI kg MO.75) 1-10 weeks after shearing in Experiment 3 was similar in magnitude to that found by other workers. Intakes of shorn sheep have been shown to increase 20-60% on pasture (Wheeler et al 1963;Wodzicka-Tomaszewska 1964); 14-43% on silagebarley diets (Morgan & Broadbent 1980;Vipond et al 1987), and 2-15% on hay diets (Ternouth & Beattie 1970;Vipond et al 1987). The increases in feed intake lasted 6-7 weeks in both non-pregnant and pregnant ewes (Wodzicka-Tomaszewska 1964;Symonds et al 1988a).…”
Section: Discussionmentioning
confidence: 99%
“…In some trials where intake of shorn ewes has been restricted to the level of unshorn ewes, lamb birth weights were not increased (Russel, Armstrong and White, 1985). Other trials have however indicated that shearing exerts its effect on lamb birth weight independently of food intake (Rutter, Laird and Broadbent, 1972;Vipond, King, Inglis and Hunter, 1987). An experiment was therefore designed to examine how these factors operate by offering shorn ewes the same silage either ad libitum or at a restricted level to give equalized intakes between shearing treatments throughout pregnancy.…”
Section: Introductionmentioning
confidence: 99%